First Screening of Heat Shock 70kDa Protein 1A (HSPA1A) Gene Polymorphisms in Indonesian Local Sheep - Sari, Apriliana Putri Zahara Nafsina Luvita; Ibrahim, Alek; Tribudi, Yuli Arif; Maulana, Yasin Pradana (Tarjih Tropical Livestock Journal, 2024)
Heat shock proteins (HSPs) are a collection of proteins that promote thermotolerance in cells and protect against environmental stress. This study was a preliminary analysis to identify the nucleotide variant within the partial heat shock 70kDa protein 1A (HSPA1A) gene in several Indonesian sheep breeds. The blood samples were collected from five breeds of Indonesian sheep (Sapudi, Batur, Sakub, Wonosobo, and Garut) to be analyzed and amplified using a specific primer. The sequences were aligned using Clustal Omega to identify the single nucleotide polymorphism (SNP). An ExPasy program was used to detect the amino acid changes. The genotyping was done by direct examination of the peak of the electropherogram. As a result, based on the sequence alignment and direct observation of the electropherograms, three variants were found: SNP c.286A>G, c.503A>G, and c.733A>G. All SNPs were categorized as synonymous mutations since they did not alter the amino acid. The genotyping of samples showed two types of genotypes (AG and GG) from each SNP. In conclusion, our study suggests exploring other regions of the HSPA1A gene to find candidate mutations for further genetic analysis.